Mucosal Vaccination Primes NK Cell-Dependent Development of CD8+ T Cells Against Pulmonary Brucella Infection - Bhagyaraj, Ella; Wang, Hongbin; Yang, Xinghong; Hoffman, Carol; Akgul, Ali; Goodwin, Zakia I.; Pascual, David W. (Frontiers in Immunology, 2021)
Past studies with the live, double-mutant B. abortus (znBAZ) strain resulted in nearly complete protection of mice against pulmonary challenge with wild-type (wt) Brucella via a dominant CD8+ T cell response. To understand the contribution innate immune cells in priming CD8+ T cell responses, mice were nasally dosed with wt B. abortus, smooth vaccine strain 19 (S19), or znBAZ, and examined for innate immune cell activation. Flow cytometric analysis revealed that znBAZ, but not wt B. abortus nor S19 infection, induces up to a 5-fold increase in the frequency of IFN-γ-producing NK cells in mouse lungs. These NK cells express increased CXCR3 and Ki67, indicating their recruitment and proliferation subsequent to znBAZ infection. Their activation status was augmented noted by the increased NKp46 and granzyme B, but decreased NKG2A expression. Further analysis demonstrated that both lung caspase-1+ inflammatory monocytes and monocyte-derived macrophages secrete chemokines and cytokines responsible for NK cell recruitment and activation. Moreover, neutralizing IL-18, an NK cell-activating cytokine, reduced the znBAZ-induced early NK cell response. NK cell depletion also significantly impaired lung dendritic cell (DC) activation and migration to the lower respiratory lymph nodes (LRLNs). Both lung DC activation and migration to LRLNs were significantly impaired in NK cell-depleted or IFN-γ-/- mice, particularly the CD11b+ and monocytic DC subsets. Furthermore, znBAZ vaccination significantly induced CD8+ T cells, and upon in vivo NK cell depletion, CD8+ T cells were reduced 3-fold compared to isotype-treated mice. In summary, these data show that znBAZ induces lung IFN-γ+ NK cells, which plays a critical role in influencing lung DC activation, migration, and promoting protective CD8+ T cell development.